The Role of Millenial Knowledge in The Application of Halal Lifestyle - Dwi Vita Lestari Soehardi (Journal of Islamic Economics (JoIE), 2022)
This study aims to determine the knowledge of millennials in the concept and application of halal lifestyles. Lifestyle can be said to be a depiction of one's self through activities and interests in everyday life. As a Muslim, you are obliged to consume everything halal. This research uses qualitative methods with a literature review. The results of this study explain the role of the millennial generation, who knows the halal concept and will apply a halal lifestyle. This finding is expected to educate the millennial generation with sustainable Islamic economic literacy to realize an attitude of self-awareness to implement a halal lifestyle.Penelitian ini bertujuan untuk mengetahui pengetahuan generasi milenial dalam konsep dan penerapan gaya hidup halal. Gaya hidup dapat dikatakan sebagai penggambaran diri seseorang melalui aktivitas dan minat dalam kehidupan sehari-hari. Sebagai seorang muslim, wajib mengkonsumsi segala sesuatu yang halal. Penelitian ini menggunakan metode kualitatif dengan kajian pustaka. Hasil penelitian ini menjelaskan bahwa peran generasi milenial yang memiliki pengetahuan tentang konsep halal akan menerapkan gaya hidup halal. Temuan ini diharapkan dapat mengedukasi generasi milenial dengan literasi ekonomi syariah yang berkelanjutan, sehingga dapat mewujudkan sikap kesadaran diri untuk menerapkan gaya hidup halal.